ANALISIS KINERJA RUAS JALAN DENGAN METODE MOVING CAR OBSERVER DAN SURVEY LALU LINTAS REGULER (STUDI KASUS : JALAN PM. NOOR) - Haryanto, Budi; Alkas, Muhammad Jazir; Aditya, Muhammad Rangga (Universitas Mulawarman, 2025)
East Kalimantan Province is designated as the prospective new capital city of Indonesia (IKN), which will experience development in various sectors, including transportation. The anticipated population growth in East Kalimantan as the new capital will lead to an increase in the number of vehicles, particularly in major cities, potentially resulting in traffic congestion. In the event of congestion, it is essential to conduct a traffic density survey, which serves as a fundamental and crucial activity to obtain traffic volume data for transportation engineering and planning purposes.This study began with data collection on traffic volume, degree of saturation, speed, and travel time using the Moving Car Observer method and the Regular Survey method. The research was conducted on PM. Noor Street, Samarinda, East Kalimantan, over three days, for three hours per day, consisting of one hour during peak hours (07:00–08:00 and 17:00–18:00) and one hour during non-peak hours (09:00–10:00). The objective was to compare road performance analysis results obtained from the two methods. Subsequently, the results were validated using the GEH and MAPE validation methods.Based on the analysis, validation using the GEH method showed that the traffic flow parameter was invalid, with only 50% of total samples meeting the criteria, while the speed and travel time parameters were valid, with 100% of samples satisfying the GEH standard, which requires more than 85% validity. In the MAPE test, the traffic flow parameter was invalid, with 67% of samples meeting the criteria, while the speed and travel time parameters were also invalid, with 0% of samples meeting the MAPE standard, which requires at least 80% validity for the “Good” and “Very Good” categories.